Isometric handgrip echocardiography: A noninvasive stress test to assess left ventricular diastolic function. Issue 12 (16th December 2017) - Jake Samuel, T.; Beaudry, Rhys; Haykowsky, Mark J.; Sarma, Satyam; Park, Suwon; Dombrowsky, Thomas; Bhella, Paul S.; Nelson, Michael D.
Abstract : Background: Cycle exercise echocardiography is a useful tool to "unmask" diastolic dysfunction; however, this approach can be limited by respiratory and movement artifacts. Isometric handgrip avoids these issues while reproducibly increasing afterload and myocardial oxygen demand. Hypothesis: Isometric handgrip echocardiography (IHE) can differentiate normal from abnormal diastolic function. Methods: First recruited 19 young healthy individuals (mean age, 24 ± 4 years) to establish the "normal" response. To extend these observations to a more at‐risk population, we performed IHE on 17 elderly individuals (mean age, 72 ± 6 years) with age‐related diastolic dysfunction. The change in the ratio of mitral valve inflow velocity to lateral wall tissue velocity (E/e'), a surrogate for left ventricular filling pressure, was used to assess the diastolic stress response in each group. Results: In the young subjects, isometric handgrip increased heart rate and mean arterial pressure (25 ± 12 bpm and 26 ± 17 mmHg, respectively), whereas E/e' changed minimally (0.6 ± 0.9). In the elderly subjects, heart rate and mean arterial pressure were similarly increased with isometric handgrip (19 ± 16 bpm and 25 ± 11 mmHg, respectively), whereas E/e' increased more dramatically (2.3 ± 1.7). Remarkably, 11 of the 17 elderly subjects had an abnormal diastolic response (ΔE/e': 3.4 ± 1.1), whereas the remaining 6 elderly subjects showed very little change (ΔE/e': 0.3 ± 0.7), independent of age or the change in myocardial oxygen demand. Conclusions: IHE is a simple, effective tool for evaluating diastolic function during simulated activities of daily living.